Healthcare: Extending x-ray vision - Eugelink, Hilde; Laureys, François (Technical Centre for Agricultural and Rural Cooperation, 2009)
Using locally developed software, doctors in three rural hospitals in Mali can send x-rays via the internet for expert diagnosis and treatment recommendations. The success of this teleradiology project has led to further e-health initiatives in the country.